Title: Arctic, Croft Title Vads Collection: Design Council Slide Collection - Designer: Brockman, Richard Manufacturer: Josiah Wedgwood & Sons Ltd (1974)
Description: Items of 'Arctic' design ceramic tableware in 'Croft' designed by Richard Brockman for Josiah Wedgwood & Sons Ltd., 1974. Includes coffee pot, covered casserole dish, salt and pepper shakers and mustard pot.